2021
DOI: 10.3390/ijms22094327
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Colorectal Cancer in the Landscape Personalized Testing—Advantages of Liquid Biopsy

Abstract: Drug-specific therapeutic approaches for colorectal cancer (CRC) have contributed to significant improvements in patient health. Nevertheless, there is still a great need to improve the personalization of treatments based on genetic and epigenetic tumor profiles to maximize the quality and efficacy while limiting cytotoxicity. Currently, CEA and CA 19-9 are the only validated blood biomarkers in clinical practice. For this reason, laboratories are trying to identify new specific prognostics and, more important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 94 publications
0
5
0
Order By: Relevance
“…The high diagnostic value of CD276 was demonstrated by a ROC curve with an AUC of 0.912 for COAD. Because the existing serum biomarkers lacked high sensitivity and speci city for the surveillance of metastatic or recurrent disease in COAD, it may be signi cant to determine the cut-off value of CD276 and use as a biomarker for early alarming tumor recurrence after surgery [23][24][25]. In addition, the clinical implication of CD276 upregulation in COAD was evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…The high diagnostic value of CD276 was demonstrated by a ROC curve with an AUC of 0.912 for COAD. Because the existing serum biomarkers lacked high sensitivity and speci city for the surveillance of metastatic or recurrent disease in COAD, it may be signi cant to determine the cut-off value of CD276 and use as a biomarker for early alarming tumor recurrence after surgery [23][24][25]. In addition, the clinical implication of CD276 upregulation in COAD was evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…(2) sEVs showed advantages far beyond other biomarkers for the diagnosis of CRC. Donatella et al found that sEVs were more sensitive than circulating tumor DNA (ctDNA) and circulating tumor cells (CTC) for the diagnosis of CRC, with higher sensitivity and specificity [ 118 ]. Furthermore, human plasma sEV-derived miRNAs had higher specificity than total plasma miRNAs in the early diagnosis of colon cancer.…”
Section: Application Of Sevs In the Diagnosis And Treatment Of Crcmentioning
confidence: 99%
“…Recent research papers [ 11 , 12 , 13 ] highlight the need for additional procedures and biomarkers in the field of precision medicine. Future steps in the clinical treatment of metastatic colorectal cancer (mCRC) will include the integration of the comprehensive knowledge of tumor gene alterations, gene expression profiling of the tumor and microenvironment, proteomic research, and host immune capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Since radiological and endoscopic imaging techniques have a low level of sensitivity for detecting the micrometastatic process, other diagnostic tools, such as liquid biopsy, are being seriously considered and implemented in the current practice. Liquid biopsies provide the possibility of tumor analysis, which includes protein and DNA/RNA analysis, i.e., molecular profiling after CTC isolation [ 12 , 19 ]. Examples include disseminated tumor cells (DTCs) in the bone marrow and CTCs in the peripheral blood, which are increasingly used as prognostic markers.…”
Section: Introductionmentioning
confidence: 99%